Designing and implementing teachers’ professional development program on crafting brain-based lessons - A. Madale, Vanjoreeh; A. Casidar, Jamaliah; B. Barquilla, Manuel; A. Salic-Hairulla, Monera; Jr G. Adil, John; R. Alcopra, Arlyn (International Journal of Evaluation and Research in Education (IJERE), 2025)
The increasing emphasis on brain-based learning (BBL) underscores its potential to enhance educational practices by integrating the biological foundations of learning. This study, conducted at Mat-I National High School, sought to address the gap between theoretical understanding and practical application of BBL among science and mathematics educators. Using a descriptive research design, the study aimed to develop and implement a comprehensive training designed to elevate teachers' proficiency in BBL strategies, ultimately improving their instructional effectiveness in science and mathematics education. A pre-training needs assessment identified a superficial familiarity with BBL among teachers, underscoring the need for more targeted professional development. The training program incorporated lectures, workshops, interactive exercises, and the creation of lesson plans tailored to BBL principles. Post-training assessments demonstrated a marked improvement in participants' understanding and application of BBL, advancing from basic to proficient levels. These findings suggest that the program successfully enhanced teaching practices. The study concludes by recommending continuous professional development, the development of BBL-aligned teaching tools, and the adoption of varied training methodologies to sustain and further improve educational outcomes in mathematics and science education.